2011
DOI: 10.1149/1.3609000
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Analysis of Reaction Mechanism of Hypophosphite Ions on Metal Surfaces

Abstract: The elementary steps of the reactions of hypophosphite ions with Cu, Ni, and Pd were calculated theoretically using Density Functional Theory (DFT) to demonstrate the reaction mechanism and gain insight at the molecular level. The elementary steps of these reactions are adsorption, dehydrogenation, and oxidation (hydroxyl base attack). In the adsorption step, hypophosphite ions adsorb onto each surface spontaneously with stabilities in the order of Ni (111) > Pd (111) > Cu (111). In the dehydrogenation step, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Our previous study showed hydrogen atom of hypophosphite ion spontaneously dissociates to migrate and provides dissociative chemisorption of hypophosphite ion on Pd surface in the case of "via H". 9 However, because P-O bond is generally strong, the case of "via O" does not involve such dissociative chemisorption of hypophosphite ion. 25 To compare adsorption affinity in these cases equally, two bonds, P-H and P-O, were fixed so that the adsorption does not involve any dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed hydrogen atom of hypophosphite ion spontaneously dissociates to migrate and provides dissociative chemisorption of hypophosphite ion on Pd surface in the case of "via H". 9 However, because P-O bond is generally strong, the case of "via O" does not involve such dissociative chemisorption of hypophosphite ion. 25 To compare adsorption affinity in these cases equally, two bonds, P-H and P-O, were fixed so that the adsorption does not involve any dissociation.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption energies of water molecule on Pd (111) and Cu (111) were calculated by Phatak et al to be ¹2.9 © 10, and ¹2.1 © 10 kJ/mol respectively. 26 Meanwhile, adsorption energies of hypophosphite on Pd (111) and Cu (111) were calculated in our previous study to be ¹84.09, and ¹49.36 kJ/mol respectively, 18 which are larger than those of water molecule. Therefore, water molecules thermodynamically have little influence on the adsorption of hypophosphite ion.…”
Section: Methodsmentioning
confidence: 96%
“…These elementary steps are (i) adsorption, (ii) dehydrogenation, and (iii) oxidation with hydroxyl group attack. 1921 In this previous study, we showed that the catalytic activities of metals on the hypophosphite ion reaction are primarily dependent on the dehydrogenation step; 18 dehydrogenation on metal surfaces with strong catalytic activity on the oxidation of hypophosphite, such as a Pd surface, must overcome only a small energy barrier to proceed, whereas dehydrogenation on surfaces with little catalytic activity, such as a Cu surface, is too destabilized to proceed. Our further analysis indicated that orbital interaction between hypophosphite and the metal surface in the adsorption step plays a critical role in initiating the dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, the complexity of the reaction mechanism for reductant oxidation makes it difficult to improve the efficiency of electroless deposition. 3 In order to obtain fundamental knowledge about the reaction mechanism of oxidation of the reductants for more precise control of the solidliquid interface in this process, we have investigated the behavior of reductants absorbed on a Cu surface from experimental and computational points of view in this paper.…”
Section: Introductionmentioning
confidence: 99%